2020
DOI: 10.3390/su12104312
|View full text |Cite
|
Sign up to set email alerts
|

Biophobia and Urban Restorativeness

Abstract: Natural areas are now known to be important resources for the health and wellbeing of urban dwellers, through, for example, the opportunities they provide for cognitive and emotional restoration. However, urban populations have also been found not to engage with these spaces and to display some form of biophobia which may hinder them from perceiving any of these benefits. This concept of biophobia is thought to entail both our innate physiological responses to the perceived danger from non-human threats such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 66 publications
(203 reference statements)
0
23
0
Order By: Relevance
“…Although the literature gives substantial evidence of the restorative benefits of nature experience (e.g., Stevenson et al, 2018;Hartig, 2021), various studies indicate that "nature" does not unequivocally elicit the approach responses that would sustain a restorative process. In a review, Patuano (2020) points to a fear of wild nature as a constraint on benefits. Nature being perceived as something scary and disgusting is put forward as a major reason, including the presence of risks of encountering dangerous and/or unattractive animals, as well as allergies, poisoning, vector-borne diseases, and getting lost due to disorientation (e.g., Bixler and Floyd, 1997).…”
Section: Nature Experience and Restorationmentioning
confidence: 99%
“…Although the literature gives substantial evidence of the restorative benefits of nature experience (e.g., Stevenson et al, 2018;Hartig, 2021), various studies indicate that "nature" does not unequivocally elicit the approach responses that would sustain a restorative process. In a review, Patuano (2020) points to a fear of wild nature as a constraint on benefits. Nature being perceived as something scary and disgusting is put forward as a major reason, including the presence of risks of encountering dangerous and/or unattractive animals, as well as allergies, poisoning, vector-borne diseases, and getting lost due to disorientation (e.g., Bixler and Floyd, 1997).…”
Section: Nature Experience and Restorationmentioning
confidence: 99%
“…Finally, university students are in a specific age range between adolescence and adulthood. Several studies looking at teenagers' use of natural spaces have found that the population to be less connected with nature than children or adults, suggesting that adolescence might be a "time out" in people's relationship with nature [39][40][41]. However, the cut-off age for this "time out" has not yet been explored.…”
Section: Cultural and Demographic Variations In The Use Of Green Spaces For Health And Wellbeingmentioning
confidence: 99%
“…It could indeed be assumed that some students are not in the habit of visiting such spaces, which might be the result of a variety of factors such as culture or previous living environments. Indeed, the use of green spaces for health and wellbeing is also linked to nature connectedness [37] and familiarity [41]. As China is undergoing rapid urbanization to the detriment of nature connectedness and contact with nature [38], Chinese students might now be more familiar with urban areas and feel less inclined to visit green spaces.…”
Section: Barriersmentioning
confidence: 99%
“…Besides these risks, some people have the perception that more vegetation can lead to risks like mosquitos, harvest mite, oak procession caterpillar, cats defecating in the garden [54]. This thinking is part of biophobia (see [59,60]), and cannot be completely tackled when it is deeply rooted. However, information about how to avoid these risks can help, for example by choosing for a mixed lay out of nature and culture, which could be less threatening than a complete natural lay out [59].…”
Section: Risksmentioning
confidence: 99%
“…This thinking is part of biophobia (see [59,60]), and cannot be completely tackled when it is deeply rooted. However, information about how to avoid these risks can help, for example by choosing for a mixed lay out of nature and culture, which could be less threatening than a complete natural lay out [59].…”
Section: Risksmentioning
confidence: 99%